2022
DOI: 10.1111/mpp.13210
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione contributes to plant defence against parasitic cyst nematodes

Abstract: Cyst nematodes (CNs) are an important group of root‐infecting sedentary endoparasites that severely damage many crop plants worldwide. An infective CN juvenile enters the host's roots and migrates towards the vascular cylinder, where it induces the formation of syncytial feeding cells, which nourish the CN throughout its parasitic stages. Here, we examined the role of glutathione (l‐γ‐glutamyl‐l‐cysteinyl‐glycine) in Arabidopsis thaliana on infection with the CN Heterodera schachtii. Arabidopsis lines with mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…Additionally, wireworm-infested roots had a significantly higher percentage of oxidized glutathione than the control group, and there was a trend towards higher levels of total glutathione in both the roots and leaves of infested plants. Similar results were found in previous studies [13,[41][42][43][44], where total glutathione levels increased in tissues at the feeding site of wheat plants after Hessian fly infestation and changes in glutathione peroxidase and glutathione transferase were found in leaves of Arabidopsis plants after infestation by Tetranycus urticae attack [41]. The role of glutathione in mediating the defense dialog during plant-wireworm interactions is not well understood, but this study provides evidence for its involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, wireworm-infested roots had a significantly higher percentage of oxidized glutathione than the control group, and there was a trend towards higher levels of total glutathione in both the roots and leaves of infested plants. Similar results were found in previous studies [13,[41][42][43][44], where total glutathione levels increased in tissues at the feeding site of wheat plants after Hessian fly infestation and changes in glutathione peroxidase and glutathione transferase were found in leaves of Arabidopsis plants after infestation by Tetranycus urticae attack [41]. The role of glutathione in mediating the defense dialog during plant-wireworm interactions is not well understood, but this study provides evidence for its involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Attention was paid not to include root tips and secondary root primordia. Subsequently, RNA extraction and qPCR were performed as previously described (Chopra et al ., 2021 ; Hasan et al ., 2022 ). ERF109 was amplified using the primers CTTATGATCGAGCCGCGATT and TCCTCCGTTCCATTGCTCTG (Cai et al ., 2014 ; Zhou et al ., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Relative expression of ERF109 was calculated based on the endogenous control 18 S rRNA (Pfaffl, 2001 ). The average ERF109 expression in the mock‐inoculated wild‐type roots of the first biological replicate was used as a reference to normalize the average expression in the other samples (Hasan et al ., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Aside from the rise in MDA, there was also an increase in GSH content. Previous research has found that decreased GSH levels affect the resilience of certain nematodes [ 63 ]. The increase in GSH could therefore be seen as an adaptive response put in place by the parasite to curb oxidative stress but which is not sufficient to compensate for stress already present.…”
Section: Discussionmentioning
confidence: 99%